Effect Of Work Stress During Pandemic Covid-19 On Employee Performance At Fuel Terminal Tasikmalaya - Pratiwi, Tiara Maulidani; Indiyati, Dian (eProceedings of Management, 2023)
The COVID-19 pandemic has had a terrible influence on Indonesia especially on human resource that termination ofemployment (LAYSOFF). PT PERTAMINA is an oil and gas mining company, one of the companies trying not tolay off employees during the COVID-19 pandemic for employees because the role of human resources is significantin the company. This study aimed to find out how the effect of work stress during the COVID-19 pandemic on theperformance of the Fuel Terminal Tasikmalaya employees. The method used in this study is a quantitative methodassisted by distributing questionnaires to 47 employees of the Fuel Terminal Tasikmalaya. The data analysis techniqueused is a simple regression analysis technique with SPSS 25 Software. Result of the hypothesis is H0 accepted, H0which shows Work Stress has no significant effect on Employee Performance. This research suggest the companiesshould conduct regular training to maximize the performance of employees who are still not in accordance with thecriteria of the company so as to minimize the occurrence of termination of employment (LAYOFFS) and for the futureresearch expected that the next researcher will conduct research with other independent variables that were not studiedin this study.Keyword: work stress, COVID-19, employee performance, SPSS 25 Software.